The composition of practice teaching in special education: A preliminary study - Shamsul Rizal Khalil; Abdul Rahim Razalli; Mohd Faiz Mohd Yaakob (Indonesian Journal of Education Methods Development, 2019)
Teaching composition of the practice teaching among teachers is important. Indeed, strategic teaching is a way of making decisions about a course, an individual class, or even an entire curriculum, beginning with an analysis of key variables in the teaching situation. This study, a preliminary study about teaching composition among special education teachers. The strategic composition namely as Quality of Instruction; The Appropriate Level of Instruction, Incentive; Time; and Lesson Plans. The findings showed Quality of Instruction is the highest level and the lowest variable is Time. Discussions and recommendations are stated for authorities and academic contribution.